Assessing local discourses on water in a South African newspaper. Issue 2 (1st February 2017) - Lawhon, Mary; Makina, Anesu
ABSTRACT: Academic understandings of environmental discourses are primarily based on global and national accounts, despite widespread acceptance of the local as an essential site of environmental action. Local water issues have been studied in a number of ways, including interviews and ethnographies that show the impacts of water scarcity, examine the role of mediating technologies, and provide diverse perspectives on governance. An overarching impression of key narratives and concerns at local scales, however, is lacking. In this paper, we examine water coverage in The Sowetan, a South African newspaper known for its distinctive voice, as a (albeit imperfect) proxy for local discourse. We identify key themes, location and scale, trigger events, actors, authors, and provide initial insights into the problem frames used in these texts. Our findings show distinct differences from the results of environmental media analyses at other scales, including strong individual citizen voices, emphasis on the politics of water, and rare use of language that accords with global environmental discourses; this also differs from results based on interviews and ethnographies at the local scale. Our findings raise important questions about the resonance of global discourse with local views and practices and how local discourses are produced, and suggest a need to more carefully examine the myriad ways of talking about justice and the environment at different scales and through different methodologies.